“Don’t Mind If I Do”: The Role of Behavioral Resistance in Self-Control’s Effects on Behavior - Gillebaart, Marleen; Kroese, Floor M. (Frontiers in Psychology, 2020)
High self-control is known to be related to the performance of behaviors that have long-term benefits, such as healthy eating. Recently, studies have suggested that people with high self-control may perform goal-directed behaviors not by exerting effortful control but rather by employing smart, effortless strategies. The current paper investigates the crucial role of behavioral resistance in explaining the relation between self-control and goal-directed behaviors: we propose that people with high self-control feel less resistance towards goal-directed behaviors compared to people with low self-control, and that this (partially) explains their increased frequency of performing these behaviors. Three cross-sectional studies were conducted in which participants reported on their level of self-control, behavioral resistance towards behaviors in the sustainability, healthy eating, exercise, and study/work domains, and their behavior in those domains. Findings consistently show that the relation between self-control and various behaviors is indeed partially mediated by behavioral resistance. It is implied that lower resistance makes it easier for people with higher self-control to perform the goal-directed behaviors, without requiring much effort. This notion yields an interesting, novel perspective on how people with high self-control manage to function so well.